PROCESS OF TEACHING FOREIGN LANGUAGES NEEDS MODERNIZATION AND CHANGES - Козлакова, Г. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
In the article the necessity of the scientifically grounded researches and created on this basis recommendations of forming educational environment, adequate to the new tasks of international activity in the field of secondary, higher, in-service professional and additional education and preparation of teachers in the conditions of international cooperation is considered. The international educational programs and projects, implementation of the British experience for improvement of higher pedagogical education and necessity of its modernization are also described